Production of Plant Secondary Metabolites from Cell and Organ Cultures under In vitro Conditions - Tuncay Çalışkan; Rüştü Hatipoğlu; Saliha Kırıcı (Turkish Journal of Agriculture: Food Science and Technology)
Plant secondary metabolites are a group of organic compounds produced by plants to interact with biotic and abiotic factors and for the establishment of defence mechanism. Secondary metabolites are classified based on their biosynthetic origin and chemical structure. They have been used as pharmaceutical, agrochemical, flavours, fragrances, colours and food additives. Secondary metabolites are traditionally produced from the native grown or field grown plants. However, this conventional approach has some disadvantages such as low yield, instability of secondary metabolite contents of the plants due to geographical, seasonal and environmental variations, need for land and heavy labour to grow plants. Therefore, plant cell and organ cultures have emerged as an alternative to plant growing under field conditions for secondary metabolite production. In this literature review, present state of secondary metabolite production through plant cell and organ cultures, its problems as well as solutions of the problems were discussed.